(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Water scarcity, reliance on agriculture and historical water misuse patterns are the major obstacles facing Central Asia, particularly Uzbekistan. In addition to these factors, there is stress on the region’s water resources due to climate change and geopolitical tensions. The aim of this article therefore is to explore the potential of Artificial Intelligence (AI) towards transforming water management in Uzbekistan and Central Asia as a whole. Through incorporating AI technologies such as machine learning, predictive analytics and Internet of Things (IoT) among others; it can lead to more sustainable use of water which is very crucial for both the economic and environmental stability of the region. Lastly, the article looks into current applications of AI within this area, outlines their advantages as well as highlights some challenges associated with AI driven water management strategies for future directions.